Development of a system for maintenance management using radio frequency and embedded systems - Melo, Marcus Vinícius Martins; Marques, Silvio Romero Adjar; Torné, Israel Gondres; Cisneros, Edry Antonio Garcia; Printes, André Luiz; Filho, Cláudio Duarte Silva; Gomes, Raimundo Cláudio Souza; Cardoso, Fábio de Sousa (Seven Editora, 2023)
Maintenance and its processes are in constant evolution. With the new trends related to maintenance 4.0 and the digitalization of administrative processes, several opportunities related to cost reduction and rational use of human resources can be observed, aiming maintenance to have an active role in the manufacturing environment. This article presents the results obtained from the implementation of a system of order request and maintenance management, using radio frequency technology (RFID) and microcontrollers, to obtain a more assertive and dynamic information flow, which results in an increase of productivity in the manufacturing sector, as well as in the administrative sector, responsible for analyzing the data generated in the maintenance cycles. The satisfactory economic evaluation of the obtained result showed the importance of the work in the search for new methods of maintenance management. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-175